Plasma levels of soluble ST2, but not IL‐33, correlate with the severity of alcoholic liver disease. Issue 2 (27th November 2018) - Sun, Zijian; Chang, Binxia; Huang, Ang; Hao, Shuli; Gao, Miaomiao; Sun, Ying; Shi, Ming; Jin, Lei; Zhang, Wei; Zhao, Jun; Teng, Guangju; Han, Lin; et al.
Abstract: Alcoholic liver disease (ALD) is a complication that is a burden on global health and economy. Interleukin‐33 (IL‐33) is a newly identified member of the IL‐1 cytokine family and is released as an "alarmin" during inflammation. Soluble suppression of tumourigenicity 2 (sST2), an IL‐33 decoy receptor, has been reported as a new biomarker for the severity of systemic and highly inflammatory diseases. Here, we found the levels of plasma sST2, increased with the disease severity from mild to severe ALD. Importantly, the plasma sST2 levels in ALD patients not only correlated with scores for prognostic models (Maddrey's discriminant function, model for end‐stage liver disease and Child‐Pugh scores) and indexes for liver function (total bilirubin, international normalized ratio, albumin, and cholinesterase) but also correlated with neutrophil‐associated factors as well as some proinflammatory cytokines. In vitro, lipopolysaccharide‐activated monocytes down‐regulated transmembrane ST2 receptor but up‐regulated sST2 mRNA and protein expression and produced higher levels of tumour necrosis factor‐α (TNF‐α). By contrast, monocytes pretreated with recombinant sST2 showed decreased TNF‐α production. In addition, although plasma IL‐33 levels were comparable between healthy controls and ALD patients, we found the IL‐33 expression in liver tissues from ALD patients was down‐regulated at both RNA and protein levels. Immunohistochemical staining further showed that the decreased of IL‐33‐positive cells were mainly located in liver lobule area. These results suggested that sST2, but not IL‐33, is closely related to the severity of ALD. Consequently, sST2 could be used as a potential biomarker for predicting the prognosis of ALD.